2022
DOI: 10.1186/s40348-022-00148-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of immune cell recruitment and BPD development

Abstract: In the neonatal lung, exposure to both prenatal and early postnatal risk factors converge into the development of injury and ultimately chronic disease, also known as bronchopulmonary dysplasia (BPD). The focus of many studies has been the characteristic inflammatory responses provoked by these exposures. Here, we review the relationship between immaturity and prenatal conditions, as well as postnatal exposure to mechanical ventilation and oxygen toxicity, with the imbalance of pro- and anti-inflammatory regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 149 publications
0
8
0
Order By: Relevance
“…Recent studies revealed that immune response plays an important role in the pathological process of BPD. 7 A genomic study conducted by Revhaug et al reported that the immune system-related genes were impacted in a murine experimental model of BPD. 8 Hyperoxia could evoke the innate immune response by promoting the generation of chemokines and cytokines and recruiting the immune cells to the pulmonary tissue in BPD model subsequently.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that immune response plays an important role in the pathological process of BPD. 7 A genomic study conducted by Revhaug et al reported that the immune system-related genes were impacted in a murine experimental model of BPD. 8 Hyperoxia could evoke the innate immune response by promoting the generation of chemokines and cytokines and recruiting the immune cells to the pulmonary tissue in BPD model subsequently.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several attempts to characterize these immune phenomena in the context of different pre- and postnatal risk factors driving BPD, comprehensive knowledge that informs diagnostic and therapeutic strategies at an early disease stage is missing. In the injured neonatal lung, both clinical and experimental studies have confirmed the presence of lung macrophages (MФ) and their respective signaling molecules ( 8 , 9 ). These key players of innate immunity undergo a complex process of maturation and are in neonates characterized by shared and distinct functions when compared to adult MФ including lipopolysaccharide-induced activation, Fc receptor-dependent phagocytosis, and differences in polarization with interferon-gamma (IFNγ) or interleukin (IL)-10 ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in fetal lungs exposed to LPS+10058F4, we observed suppression in IL1β and CXCL1 compared to LPS-exposed group, and suppression in TNF-α compared to both controls and LPS-exposed group. IL1β, TNF-α and CXCL1 dysregulation are well-associated with IAI and BPD ( Ambalavanan et al, 2009 ; Cappelletti et al, 2020 ; Heydarian et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%